The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.ejmp.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of computing parameters and measurement locations on the estimation of 3D NPS in non-stationary MDCT images

Abstract: The goal of this study was to investigate the impact of computing parameters and the location of volumes of interest (VOI) on the calculation of 3D noise power spectrum (NPS) in order to determine an optimal set of computing parameters and propose a robust method for evaluating the noise properties of imaging systems. Noise stationarity in noise volumes acquired with a water phantom on a 128-MDCT and a 320-MDCT scanner were analyzed in the spatial domain in order to define locally stationary VOIs. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Noise Power Spectrum: Image noise was quantified and characterised by computing noise power spectra (NPS) according to the recommendations from the International Commission on Radiation Units and Measurements Reports 54 and 87, and the method described by Miéville et al . 3638 . Measurements were performed on 40 consecutive axial MDCT images taken at the phantom extremity and containing only water (no central insert).…”
Section: Methodsmentioning
confidence: 99%
“…Noise Power Spectrum: Image noise was quantified and characterised by computing noise power spectra (NPS) according to the recommendations from the International Commission on Radiation Units and Measurements Reports 54 and 87, and the method described by Miéville et al . 3638 . Measurements were performed on 40 consecutive axial MDCT images taken at the phantom extremity and containing only water (no central insert).…”
Section: Methodsmentioning
confidence: 99%
“…Burgess (Burgess et al, 2001a), Bochud (Bochud et al, 1999), and others (Heine et al, 1999) have defined the total noise power spectrum, NPS t ( f ), as the sum of the anatomical noise power spectrum, NPS a ( f ), and the quantum noise power spectrum, NPS q ( f ),: NPStfalse(ffalse)=NPSqfalse(ffalse)+NPSafalse(ffalse) The quantum noise power spectrum is a fundamental analytical tool in detector design, development, and assessment, and has been used extensively in the evaluation of x-ray based medical imaging systems (Yang et al, 2008, Miéville et al). The anatomical noise power spectrum has been discussed in a more limited manner (Bochud et al, 1999, Burgess, 1999, Metheany et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…When investigating the empirical relationship with actual reconstruction filters, which range from ramp-like standard filters with conventional apodisation functions, to edge-enhancing high spatial resolution filters, it was found that the relationship was closer to a power of 4 or 5 [29,42]. (28) This is illustrated in the following graph ( Fig. 7a), for the body scans.…”
Section: Spatial Resolution (Fav)mentioning
confidence: 99%